2016
DOI: 10.4273/ijvss.8.1.07
|View full text |Cite
|
Sign up to set email alerts
|

H∞ Control of Active Suspension System for a Quarter Car Model

Abstract: In recent years, the use of active control mechanisms in active suspension systems has attracted considerable attention. The main objective of this research is to develop a mathematical model of an active suspension system that is subjected to excitation from different road profiles and control it using H∞ technique for a quarter car model to improve the ride comfort and road handling. Comparison between passive and active suspension systems is performed using step, sinusoidal and random road profiles. The per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Another comparison based on the quarter model, but between a robust PI and Linear Quadratic Regulator (LQR) controller, was conducted by [6], where they showed that the LQR outperformed the PI controller in the presence of parameter uncertainty. Another optimal controller is H ∞ , which was examined by [7] and showed a 93% reduction in the car's acceleration, wheel travel, and suspension travel.…”
Section: Introductionmentioning
confidence: 99%
“…Another comparison based on the quarter model, but between a robust PI and Linear Quadratic Regulator (LQR) controller, was conducted by [6], where they showed that the LQR outperformed the PI controller in the presence of parameter uncertainty. Another optimal controller is H ∞ , which was examined by [7] and showed a 93% reduction in the car's acceleration, wheel travel, and suspension travel.…”
Section: Introductionmentioning
confidence: 99%
“…where is damping force of MD; is plastic viscosity of liquid; is offset force; 1 , are shown in Figure 2. Figure 3 displays the physical model of a researched quarter suspension, according to which its mathematic model can be expressed by the following [29]:…”
Section: Modeling Of Pmmvmd Suspensionmentioning
confidence: 99%
“…Suspension systems are designed to reduce the transmission of vibration from road surface disturbances. Semi active and active suspension systems have been more attractive for researchers during the last several decades [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that controlled suspension can provide much better performance in the ride comfort compared with uncontrolled system. In the study by Nouby et al [10] a quarter vehicle active suspension control model is *Corresponding Author Email: a.saghafi@birjandut.ac.ir (A. Saghafi) developed.…”
Section: Introductionmentioning
confidence: 99%